The Effects of Intrinsic Motivation and Affective Commitment On Employee Performance: Does Organizational Culture Matter? - Bagus Wibowo; Abd. Rasyid Syamsuri; Prima Andreas (International Journal of Science and Environment (IJSE), 2026)
Employee performance is a critical factor in achieving organizational effectiveness and sustainability. Although previous studies have extensively examined the effects of intrinsic motivation, affective commitment, and organizational culture on employee performance, inconsistent findings remain regarding the influence of motivation on performance, and limited evidence exists concerning the simultaneous moderating role of organizational culture in the relationships between intrinsic motivation, affective commitment, and employee performance, particularly within the agribusiness sector. Therefore, this study aims to analyze the effects of intrinsic motivation and affective commitment on employee performance, with organizational culture serving as a moderating variable at PT. Indojaya Agrinusa Hatchery Unit Pekanbaru. This study employed a quantitative approach. The sample consisted of 71 employees selected using a census technique from the total population of employees at PT. Indojaya Agrinusa Hatchery Unit Pekanbaru. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that intrinsic motivation has a positive and significant effect on employee performance. Affective commitment also has a positive and significant effect on employee performance. Furthermore, organizational culture has a positive and significant direct effect on employee performance. However, organizational culture does not significantly moderate the relationship between intrinsic motivation and employee performance, nor does it significantly moderate the relationship between affective commitment and employee performance. The coefficient of determination analysis reveals that the model explains 52.9% of the variance in employee performance. The findings imply that organizations should prioritize strategies aimed at strengthening employees’ intrinsic motivation, emotional attachment, and organizational culture to improve performance. This study contributes to the human resource management literature by providing empirical evidence from the Indonesian hatchery industry and demonstrating that organizational culture functions primarily as a direct determinant of employee performance rather than as a moderating mechanism.